The dimensions of soil security - McBratney, Alex; Field, Damien J.; Koch, Andrea (Geoderma, 2014)
Soil security, an overarching concept of soil motivated by sustainable development, is concerned with the maintenance and improvement of the global soil resource to produce food, fibre and fresh water, contribute to energy and climate sustainability, and to maintain the biodiversity and the overall protection of the ecosystem. Security is used here for soil in the same sense that it is used widely for food and water. It is argued that soil has an integral part to play in the global environmental sustainability challenges of food security, water security, energy sustainability, climate stability, biodiversity, and ecosystem service delivery. Indeed, soil has the same existential status as these issues and should be recognized and highlighted similarly. The concept of soil security is multi-dimensional. It acknowledges the five dimensions of (1) capability, (2) condition, (3) capital, (4) connectivity and (5) codification, of soil entities which encompass the social, economic and biophysical sciences and recognize policy and legal frameworks. The soil security concept is compared with the cognate, but more limited, notions of soil quality, health and protection. •Society's sustainability is facing six existential global environmental challenges.•These challenges may be addressed by the new concept of soil security.•Soil security has relationships with soil quality, soil health and soil protection.•Soil security is a much wider concept framed using five dimensions.•The dimensions are soil capability, condition, capital, connectivity & codification.